Analisis perubahan panjang dan tingkat tegangan terhadap jumlah lilitan pegas koil dengan menggunakan software ANSYS dan Autodesk Inventor - Fauzan, Shafwan; Boni Sena (Universitas Muhammadiyah Metro, 2024)
Coil springs are important components used in vehicles or machinery for vibration damping and load-bearing systems. Made of spiral-shaped steel, coil springs function to absorb the energy received. In vehicles, these springs help absorb vibrations and loads, thus providing a comfortable and safe ride. To ensure its strength, coil springs are tested by various methods, one of which is the finite element method. This method uses numerical techniques for structural analysis through simulations using software such as ANSYS and Autodesk Inventor. This simulation aims to compare the results of coil springs with variations in the number of turns. The results show that the coil spring with 10 turns has the lowest maximum stress and the highest displacement. The difference in results between the two software is due to the difference in problem solving methods. According to the simulations, the best material for the coil spring with 10 turns is high carbon steel according to ANSYS and nickel-cobalt-chrome alloy according to Autodesk Inventor.